1998
DOI: 10.1149/1.1838723
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Metal Ions onto Hydrophilic Silicon Surfaces from Aqueous Solution: Effect of pH

Abstract: This work examines the pH and time dependence of metal deposition onto hydrophilic silicon surfaces. We find that the surface concentration of metal species is proportional to the pH. Time dependence is seen for only a few metals, notably Cr and Fe in this study, especially at high pH. Si surfaces with wet chemical oxides were exposed to a dilute solution of ten metals: Al, Ba, Ca, Cr, Cu, Fe, K, Ni, Sr, and Zn, in dilute nitric acid solution, from pH 3 to 5.6, for different periods of time, from about 1 to 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 2 publications
0
28
0
1
Order By: Relevance
“…Discussion Relationship between model and theoretical coefficients.-Equation 12 is a generalized form of Eq. 9 log SiOM ϭ Const ϩ m(pH) ϩ n(pM) ϩ p log [12] We can obviously relate the theoretical coefficients, m, n, and p, in Eq. 12 to the empirical, model coefficients, a 1 , a 2 , and a 3 of Eq.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Discussion Relationship between model and theoretical coefficients.-Equation 12 is a generalized form of Eq. 9 log SiOM ϭ Const ϩ m(pH) ϩ n(pM) ϩ p log [12] We can obviously relate the theoretical coefficients, m, n, and p, in Eq. 12 to the empirical, model coefficients, a 1 , a 2 , and a 3 of Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Loewenstein and Mertens, on the other hand, found that cations are the adsorbing species in acidic solution. 12 All of these studies lack a comprehensive model relating the concentrations of adsorbing species in solution to the resulting metal concentrations on the wafer surface. While we know that materials in solution somehow end up on the silicon surface, we do not know the relationship between solution and surface concentration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On a silicon surface, since there are no SiNH 2 sites, only interactions described by Eqs. (2) and (3) take place [15,16]. The de¯ection of the cantilever should be due to the sum of all the interactions happening at the surface and the effect of the electrolyte layer on the silicon surface [16].…”
Section: Deflection Of Au-coated Cantilevers In Different Ph Solutionsmentioning
confidence: 99%
“…4.22 Uma característica importante nos óxidos de silício é que estes compostos em meio aquoso estabelecem espontaneamente cargas negativas em sua superfície [20,36,62]. …”
Section: Avaliação Em Meio Poroso Constituído De Pós De Vidro "B"unclassified